Pradimicin U, a promising antimicrobial agent isolated from a newly found Nonomuraea composti sp. nov - Duangupama, Thitikorn; Pittayakhajonwut, Pattama; Intaraudom, Chakapong; Suriyachadkun, Chanwit; Tadtong, Sarin; Kuncharoen, Nattakorn; He, Ya Wen; Tanasupawat, Somboon; Thawai, Chitti (My University, 2024)
Pradimicin U is a new dihydrobenzo[a]naphthacenequinone compound found to be active on a screen designed to investigate compounds with antimicrobial activity, produced by the actinomycete designated strain FMUSA5-5T. The strain was isolated from a bio-fertilizer of Musa spp. collected from Suphanburi province, Thailand. The chemotaxonomic characteristics and 16S rRNA gene analysis revealed that strain FMUSA5-5T is a member of the genus Nonomuraea. Low genome-based taxonomic criteria, average nucleotide identity (ANI) (82.8–88.3%), average amino-acid identity (AAI) (79.4–87.3%), and digital DNA–DNA hybridization (dDDH) (29.5–38.5%) values and several phenotypic differences between strain FMUSA5-5T and its closest type strains of the genus Nonomuraea indicated that strain FMUSA5-5T represents a novel species of the genus Nonomuraea and the name Nonomuraea composti sp. nov. is proposed for the strain. The crude extract from the culture broth of strain FMUSA5-5T displayed promising antimicrobial activity against several pathogens and led to the isolation of a novel secondary metabolite, pradimicin U. Interestingly, this compound displayed a broad spectrum of biological activities such as antimalarial activity against Plasmodium falciparum K1 (IC50 value = 3.65 µg/mL), anti-Mycobacterium tuberculosis H37Ra (MIC value = 25.0 µg/mL), anti-Alternaria brassicicola BCC 42724 (MIC value = 25.0 µg/mL), anti-Bacillus cereus ATCC 11778 and anti-Staphylococcus aureus ATCC 29213 (MIC values = 6.25 and 1.56 µg/mL, respectively). Moreover, the compound possessed strong anti-human small cell lung cancer (NCI-H187) activity with IC50 value of 5.69 µg/mL, while cytotoxicity against human breast cancer (MCF-7) and Vero cells was very weak (IC50 values of 52.49 and 21.84 µg/mL, respectively).
Keywords: Nonomuraea; Polyphasic taxonomic characterization; Pradimicin U; Whole-genome sequence analysis